Synodality and Ministry in the Eastern Churches - Maniyattu, Pauly (Asian Horizons, 2025)
Synodality of the Church is an essential manner of her existence. The Eastern Churches maintained synodality without much cessation, remaining faithful to the synodal character of the early Church. The present study focuses on the synodal character of the ministry in the Church, especially in the Eastern Churches. First of all, this study analyses the scriptural foundation of the synodality of the Church, especially seen in the Acts of the Apostles (Acts 1:15-26; 6:1-6; 15: 22-35). The Eastern Churches see the foundation of the synodality of the Church in the Holy Trinity, which is manifested in the gathering together of the congregation for the Eucharist. According to the Eastern Churches, the Roman primacy does not contradict the synodal character of the Church. Even those Churches which are not in full communion with Rome, recognize the primacy of Rome, though not in the exact understanding held by the Catholic Church today. In the East, the bishop exercises his ministry keeping its synodal dimension. The bishop is obliged to keep synodality in his relation with other bishops, priests, deacons and other clerics of his eparchy, and with the religious and lay faithful. The Church of St Thomas Christians has a great testimony of synodality. In the history of St Thomas Christians, we can find the synodality profoundly presented in the various levels of ecclesial life.